Taxation of copper and nickel ores mining in Australia, Canada, Chile, Kazakhstan and USA - N. S. Kostrykina; A. V. Korytin; E. V. Melkova (Правоприменение, 2022)
The subject. This article discusses the taxation of copper and nickel extraction in Australia, Canada, Chile, Kazakhstan and USAThe purpose of the article is to confirm or disprove the hypothesis that the experience of taxation of copper and nickel extraction in Australia, Canada, Chile, Kazakhstan and USA may be used for modifying the mineral extraction tax (MET) in Russia in order to increase the share of resource rent collected by the government.The methodology of research includes legal interpretation and economic analysis of the tax legislation in United States, Canada, Australia, Chile and Kazakhstan as countries with a well-developed tax system and a significant size of the mining sector in overall GDP.The authors select the legislative acts of these countries and regions that determine the procedure for collecting taxes in the extraction of metal ores, including those containing copper and nickel, as well as in the production of copper and nickel. The selected legislative acts are analyzed to determine the essential parameters of taxation. Particular attention is paid to the method of calculating the tax base, taking into account the approach to assessing the value of the taxable object, permissible tax deductions and exceptions, which allows authors to test the hypothesis put forward by determining which part of the value of a mineral resource is withdrawn during taxation.The main results, scope of application. Mineral extraction tax is the main tool for collecting natural resource rent in Russia. However, the level of taxation of solid minerals and coal is disproportionately low compared to their share in the production and export of raw materials. Thus, in 2018, the amount of MET on all minerals totaled 100.5 billion rubles, while the MET collected from oil and natural gas amounted to 5,979.6 billion rubles, i.e. 60 times as much. At the same time, the role of solid minerals in the Russian economy is comparable to the role of oil and gas. The share of the main types of minerals in the exports of the Russian Federation in 2018 was 20.4% compared to 56% for oil and gas, i.e. the difference of less than three times. The contribution of the industries related to the extraction of minerals and production of metals (mining of coal, ores, diamonds, metallurgy, fertilizer production) to the Russian GDP is about half as much as that of industries involved in the extraction and processing of oil and natural gas (7% and 14% of GDP respectively).In view of the above, it is important to develop a new approach to the taxation of solid minerals in Russia based on the world’s best practices. In order to identify the general principles of their taxation, we have conducted a detailed analysis of the tax legislation in a number of countries with a well-developed tax system and a significant size of the mining sector (the United States, Canada, Australia, Chile and Kazakhstan). We focused on the taxation of copper and nickel ores mining.Conclusions. The analysis of the international experience of taxation of copper and nickel mining sector reveals the following trend: the tax is calculated based on the market value of the extracted minerals, which is linked to the price quotes for the relevant product on an organized metal exchange (for example, the price of pure metal on the London Metal Exchange). This approach can be used in the Russian tax practice in several ways. First, Russia can adopt the Australian model where royalty on a mineral resource can be levied at the time of sale of the useful component irrespective of the processing stage (ore, concentrate or metal). The second potential model is based on the actual sale price of the product (provided it is sold in an arm’s length transaction) after deducting the costs of processing (i.e., smelting, enrichment etc., depending on the stage of processing) to arrive at the market value of the ore at the "mine mouth". The third is the Canadian model which is similar to the second one, but with the extraction costs also deducted from the sale price.